Who Controls the Public Debt? A Critical Review of Sandy Brian Hager's Public Debt, Inequality, and Power - Christopher Mouré (Capital as Power - Toward a New Cosmology of Capitalism, 2024)
Hager's project examines the historical development of US public debt ownership and its political implications. His main innovation is to approach the topic from the perspective of disaggregated social class and frame questions of public debt ownership in terms of social inequality and power. He tackles four questions: who are the owners of the public debt; what are the distributional effects on income and wealth; what are the implications of increasingly foreign public debt ownership; and what is the relationship between debt-ownership concentration and political influence. He argues that the increasingly unequal power of bondholders undermines the ability of the US government to pursue a more equitable and democratic fiscal policy, which is essential to tackling a range of social issues (including inequality itself). The project is illuminating and has important political implications, though due to the narrow scope of the project, Hager gives light treatment of some key aspects of the relationship between debt and power.
Keywords: P1; H6; 330; capital as power; distribution; policy; public debt; ownership